AB0546 The prevalence of inflammatory back pain in a uk primary care population. (23rd January 2014) - Hamilton, L. E.; Macgregor, A.; Warmington, V.; Pinch, E.; Gaffney, K.
Abstract : Background: Inflammatory back pain (IBP) is the earliest and commonest symptom of axial spondyloarthropathy (SpA). SpA can be difficult to diagnose in its early stages, but the identification of patients with IBP may offer a cost-effective way to reduce diagnostic delay by targetting investigations appropriately. Objectives: We determined the prevalence of IBP in a UK primary care population using three published IBP criteria: Calin, Berlin and ASAS. Methods: The study took place in a large general practice in Norfolk, UK, with 17, 177 registered patients. Potential participants aged 18-80 years were identified from their primary care records as having consulted on at least one occasion with low back pain. A self-completed screening questionnaire was sent to a random sample of 978 patients asking about IBP symptoms. A further questionnaire was sent to non-responders. Patients were excluded from the study if they required nursing home care or had a terminal diagnosis. Results: Five hundred and five completed questionnaires were returned (response rate 51.6%). Respondents had a median age of 60 years (IQR 48-67) and 44.8% were male. Eighty percent reported back pain of at least 3 months duration. The ASAS IBP criteria were fulfilled by 75 (14.9%) respondents, the Calin criteria by 132 (26.1%) and the Berlin criteria by 151 (29.9%). IBP was seen more commonly in women, but this difference was not statistically significant and there was no significant difference in prevalence between different age bands. The prevalence of IBP among patients with at least one previous consultation for back pain was 7.7% (95% CI 6.2, 9.5%) using the ASAS criteria, 13.5% (11.5, 15.8) using the Calin criteria and 15.4% (13.3, 17.8) using the Berlin criteria. Conclusions: Estimations of the prevalence of IBP are significantly affected by the criteria chosen for classification. This should be considered when comparing studies, and when assessing patients in the clinical setting. Disclosure of Interest: L. Hamilton Grant/research support from: Pfizer, Speakers bureau: MSD, A. Macgregor: None Declared, V. Warmington: None Declared, E. Pinch: None Declared, K. Gaffney Grant/research support from: Pfizer, Speakers bureau: Pfizer, UCB, Abbott